Multiculturalism in Malaysian children's literature in english: a study of K. S. Maniam's Top winner and Shirley Geok-Lin Lim's Princess Shawl - Mohd. Ezamir Azral bin Mohd. Azrul (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2011)
This thesis is a critical analysis of multiculturalism as depicted in two Malaysian children's novels written in English: K. S. Maniam's Top Winner and Shirley Geok-lin Lim's Princess Shawl. It takes as its framework the American multicultural education theory as well as writings on multicultural education and literature in Malaysia in order to highlight the novels' advocacy of shared cultural values as the most important aspect of multiculturalism in the country. Disregarding ethnicity as the foundation for multiculturalism, this study argues that this also requires a reconfiguration of intersecting concepts such as gender and history in order to assert the importance of removing gender bias in literature and the preservation of traditional values and lifestyle. The genre of the two works, contemporary realism and fantasy respectively, also aid in their representation of multiculturalism as one draws upon the realism of life in the country while the other reconstructs a pivotal moment in the multicultural history of the country. Despite the differences in genre, both works look to the past for lessons in appreciating cultural values even while engaging, as in the case of Top Winner, with modern technology brought about by globalization, in particular, the Internet.